The virus plague / Nur Zakri Haji Zakaria and Marini Haji Othman (Universiti Teknologi MARA, Terengganu, 1991)
This paper attempts to shed some light on the subject of the computer virus. Most of the confusion amongst computer users regarding viruses is due mainly to the lack of technical know-how or misinformation.